Hemodynamic Monitoring Using Echocardiography in the Critically Ill - de Backer, Daniel; Cholley, Bernard P.; Slama, Michel; Vieillard-Baron, Antoine; Vignon, Philippe (Springer Berlin Heidelberg : Imprint: Springer, 2011)
The hemodynamic evaluation of patients with acute circulatory failure and respiratory failure has in the past usually been performed using invasive procedures but in recent years less invasive monitoring devices have been introduced. Hemodynamic evaluation by echocardiography is based on the integration of simple indices that can be easily acquired within a few minutes at the bedside. Echocardiography can be used for both the diagnosis and the management of circulatory and respiratory failure. This book provides all the essential information required by readers in order to perform optimal hemodynamic management of the critically ill based on echocardiographic guidance. After an introductory section on basic principles, hemodynamic assessment using echocardiography is discussed in detail. The diagnosis and management of all types of circulatory and acute respiratory failure by means of echocardiography are then rigorously considered, and specific situations such as thoracic trauma and acute aortic syndrome are examined. The final section is devoted to future issues and applications.